Unpacking Reward Shaping: Understanding the Benefits of Reward Engineering on Sample Complexity - Gupta, Abhishek; Pacchiano, Aldo; Zhai, Yuexiang; Kakade, Sham; Levine, Sergey (2022)
Abstract to come...